1979
DOI: 10.1029/rg017i008p01923
|View full text |Cite
|
Sign up to set email alerts
|

Organic chemistry on Titan

Abstract: Observations of nonequilibrium phenomena on the Saturn satellite Titan indicate the occurrence of organic chemical evolution. Features taken from various models of Titan's atmosphere are combined in a working composite model that provides environmental constraints within which different pathways for organic chemical synthesis are assessed. Experimental results and theoretical modeling studies suggest that the organic chemistry of the satellite is dominated by two atmospheric processes: photochemistry and energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…The formation of HCN from the irradiation of CH 4 and N 2 mixtures at wavelengths > 125 nm was first reported by Dodonova (1966), with an approximate yield of 10 -5 HCN molecules per photon (Chang et al, 1979). This result was derived by using a very specific detection technique sensitive only to gas-phase HCN, with corroboration from measurement of trapped gases with a mass spectrometer.…”
Section: Photochemical Formation Of Cn Bondmentioning
confidence: 56%
See 1 more Smart Citation
“…The formation of HCN from the irradiation of CH 4 and N 2 mixtures at wavelengths > 125 nm was first reported by Dodonova (1966), with an approximate yield of 10 -5 HCN molecules per photon (Chang et al, 1979). This result was derived by using a very specific detection technique sensitive only to gas-phase HCN, with corroboration from measurement of trapped gases with a mass spectrometer.…”
Section: Photochemical Formation Of Cn Bondmentioning
confidence: 56%
“…Interestingly, when other workers in the 1970s and early 1980s attempted to repeat the results of Dodonova (1966) but failed to produce nitriles or N-containing organics in the UV (Ferris and Chen, 1975;Chang et al, 1979;Bossard et al, 1982;Raulin et al, 1982), Bossard et al (1982) concluded that ''UV light is not able to produce nitriles from CH 4 -N 2 mixtures'' and ''UV light is not an efficient source for producing unsaturated carbon chains.'' The results presented herein clearly contradict those conclusions.…”
Section: Trainer Et Almentioning
confidence: 99%
“…Similar to the spectrum of terrestrial ability of convection energy (Flasar 1983, Lindal et al 1983 and condensable species in the lower atmosphere make it lightning (Orville andHenderson 1984, Wiedman et al 1989), the red portion of the spectrum is dominated by conceivable that some form of lightning discharge could be occurring (Chang et al 1979, Gupta et al 1981, Borucki atomic line radiation from the excited states of the neutral atoms, and the blue portion of the spectrum is dominated et al. 1984).…”
Section: Measurement Protocolmentioning
confidence: 95%
“…This basic picture of the organic nature of Titan's atmosphere (reviewed by Chang et al, 1979) was conÿrmed by the Voyager observations of Titan in 1980. Voyager images showed an optically thick haze in the stratosphere completely obscuring the surface at visible wavelengths (Smith et al, 1981.…”
Section: Introductionmentioning
confidence: 99%